1999
DOI: 10.1063/1.479835
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectrum of the CH2 out-of-plane fundamental of C2H5

Abstract: Measurements of the ethyl radical -CH2 out-of-plane rocking vibrational fundamental by transient diode laser absorption spectroscopy are reported. The new data provide information on the structure of, and the barrier to internal rotation in, the radical, and how these quantities change on vibrational excitation. We find that the effective barrier decreases from approximately 17 cm−1 in the zero point level to 10 cm−1 in the excited vibrational level. The assigned data set now contains approximately 450 rotatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…This is a section of the Q branch of the K ϭ 1 4 0 subband in the HCBr à 1 AЉ-X 1 AЈ origin band. It was originally recorded by Marr et al (15), but the room-temperature spectrum shown here was recorded more recently using a Herriott-type multipass absorption cell (21), which provided a factor of 8 -10 improvement in absorption sensitivity. In contrast to the K ϭ 0 4 1 subband, it is not possible to recognize any regularity in this spectrum, and the expected doubling due to the 79/81 Br isotope structure cannot be simply identified.…”
Section: Results and Rotational Assignmentsmentioning
confidence: 99%
“…This is a section of the Q branch of the K ϭ 1 4 0 subband in the HCBr à 1 AЉ-X 1 AЈ origin band. It was originally recorded by Marr et al (15), but the room-temperature spectrum shown here was recorded more recently using a Herriott-type multipass absorption cell (21), which provided a factor of 8 -10 improvement in absorption sensitivity. In contrast to the K ϭ 0 4 1 subband, it is not possible to recognize any regularity in this spectrum, and the expected doubling due to the 79/81 Br isotope structure cannot be simply identified.…”
Section: Results and Rotational Assignmentsmentioning
confidence: 99%
“…Although the ethyl radical exhibits significant coupling between torsion, CH 2 -bending, and CH-stretching coordinates, the rotational, torsional, and nuclear-spin symmetries can, nevertheless, be characterized in a zeroth-order basis as a hindered internal rotor with a small barrier. 24,25,28 Quantum labels for this basis include ͑i͒ total angular momentum ͑J͒, which is rigorously conserved; ͑ii͒ projection on the molecule fixed frame ͑k͒, which is conserved only for a perfect symmetric top; and ͑iii͒ internal rotor angular momentum ͑m͒ for relative rotation between methylene and methyl groups, which is conserved ͑neglecting Coriolis effects͒ in the zero-barrier limit. The low barrier makes H-atom interchange a feasible process for both CH 3 and CH 2 , resulting in a direct product of the spin symmetries of the methyl and methylene subunits with 4:2 and 3:1 statistical weights, respectively.…”
Section: A Group Symmetry Analysis and Predictionsmentioning
confidence: 99%
“…[17][18][19] Notably more elusive in these gas-phase efforts have been members of the simply alkyl radical family, the rotationally resolved spectra of which have been reported only for methyl 18,[20][21][22][23] and selected vibrational modes of the ethyl radical. [24][25][26] This paucity of information is, at first, quite surprising, since saturated alkyl radicals are abundant intermediates in fossil fuel combustion phenomena and readily generated by simple atom abstraction from alkanes. One experimental difficulty in studies of saturated alkyl radicals is that they typically have no bound or quasibound electronically excited states, greatly limiting the use of sensitive laser-induced fluorescence ͑LIF͒ and resonance-enhanced multiphoton ionization ͑REMPI͒ schemes.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations